Inclusion as Top-Priority Activity of the Moscow State University of Psychology and Education (Outcomes of the Moscow International Education Fair-2018) - Shvedovskaya A.A.,; Erkenova F.S. (Психологическая наука и образование, 2018)
The article presents the results of the main directions of the exposition activity of the Moscow State University of Psychological and Education (MSUPE) presented at the 5th Moscow International Education Fair (MIEF), which was held April 18—21, 2018 in Moscow. The inclusive education was the key theme for the Moscow State University of Psychological and Education at MIEF. The content component of the university's exposure: three clusters, seven speakers, more than 60 thematic stands. Attention is drawn to the breadth of the participation of the MSUPE in discussing the issues of the ecosystem of education.